Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1067/mnc.2000.107242
|View full text |Cite
|
Sign up to set email alerts
|

Fourier phase analysis of SPECT equilibrium radionuclide angiography in symptomatic patients with mitral valve prolapse without significant mitral regurgitation: Assessment of biventricular functional abnormalities suggesting a cardiomyopathy

Abstract: Symptomatic patients with MVP frequently have ventricular dysfunction in 1 or both ventricles, sometimes limited but more marked in the presence of severe VA even without significant mitral regurgitation, suggesting structural modification. The use of a sensitive, accurate, and 3-dimensional method such as single photon emission computed tomography equilibrium radionuclide angiography may be of interest for a noninvasive investigation, especially in young symptomatic patients with MVP and VA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…30 However, these changes in deformations may be the first signs of future deterioration of the left ventricular systolic function by mitral valve prolapse progression. [16][17][18] Moreover, we found aortic root enlargement in young patients with prolapse. Mitral valve prolapse associated with aortic root enlargement is an independent predictor of greater aortic size not only in patients with systemic connective tissue disorders such as Marfan syndrome, but also in the general population.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…30 However, these changes in deformations may be the first signs of future deterioration of the left ventricular systolic function by mitral valve prolapse progression. [16][17][18] Moreover, we found aortic root enlargement in young patients with prolapse. Mitral valve prolapse associated with aortic root enlargement is an independent predictor of greater aortic size not only in patients with systemic connective tissue disorders such as Marfan syndrome, but also in the general population.…”
Section: Discussionmentioning
confidence: 69%
“…Left ventricular contraction abnormalities in symptomatic mitral valve prolapse patients without severe mitral regurgitation but with ventricular arrhythmias have been described in some studies using cardiac tomography, radionuclide angiography, and single-photon emission computed tomography. [16][17][18] Moreover, a marked reduction in the myocardial deformation indices has been demonstrated in patients with degenerative severe mitral regurgitation. 19,20 Two-dimensional speckle-tracking echocardiography is a relatively new technique used for evaluation of the myocardial function.…”
Section: N Inherited Connective Tissue Disorders Thatmentioning
confidence: 99%
“…Вопрос о возможности снижения сократимости при первичном ПМК ставился ранее на основании исследований с использованием компьютерной томографии, радионуклидной ангиографии и одно-фотонной эмиссионной компьютерной томографии [8][9][10]. Было показано снижение показателей дефор-мации миокарда (strain) у пациентов с тяжелой деге-неративной МН [11,12].…”
unclassified
“…Both planar and SPECT RNA studies have demonstrated that phase analysis parameters could assess MD by characterizing abnormal cardiac (67,(78)(79)(80)(81) patterns and be a predictor of cardiac events (74,82). Other studies have also shown that phase analysis could differentiate between normal and MD patients with high accuracy (65,68,69,83…”
Section: Dyssynchrony Evaluationmentioning
confidence: 99%